Improving Students' Mathematics Learning Outcomes on Settings Through The Think Pair Share (TPS) Cooperative Learning Model in Class VII-2 SMP Negeri 9 Kendari - La Singga, S.Pd La Singga (Amanah: Jurnal Amanah Pendidikan dan Pengajaran, 2022)
This Classroom Action Research aims to improve the learning outcomes of class VII-2 SMP Negeri 9 Kendari on the subject of the Association through a cooperative learning model using the Think-Pair-Share (TPS) type. The subjects in this study were grade VII-2 students of SMP Negeri 9 Kendari for the academic year 2021/2022 with a total of 38 students. The implementation consists of 3 cycles. Each cycle under study is adjusted for changes as designed in the investigated factors. The procedure of this research: (1) planning, (2) implementing actions, (3) observation and evaluation, and (4) reflection. Resources are students and teachers. The types of data obtained are qualitative data through observation sheets and journals and quantitative data through learning outcomes tests. The results showed that the implementation of this learning scenario reached 70.45% in the first cycle, 75.71% in the second cycle and 86.21% in the third cycle. In terms of results, student learning outcomes have increased each cycle. In the first cycle, students who scored 75 reached 60.53%, 76.32% in the second cycle and 89.47% in the third cycle.